2020
DOI: 10.3349/ymj.2020.61.7.614
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Trend and Characteristics of Korean Adolescents Presenting to Emergency Department for Self-Harm: A 5-Year Experience, 2015 to 2019

Abstract: Purpose: Emergency department (ED) is a common treatment setting for adolescents with clinically serious self-harm. Here, we investigated the clinical characteristics and trends of adolescents with self-harm who visited the ED in one Korean university hospital. We also compared patients with a single ED visit to those with multiple ED visits to identify the risk factor of repeated visits. Materials and Methods: We retrospectively identified patients aged 12 to 18 years who presented to ED for self-harm from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…In this study, we found that the incidence rates of SA-related ED visits was increasing in female adolescents from 2016 to 2019. This finding is consistent with results reported in previous studies conducted in Korea about the increase in number of female teenagers engaging in suicidal behaviors, including SA as well as suicidal ideation and suicidal planning [ 6 , 29 ]. The increase in SAs among female seems to contribute to the stagnation of the suicide rate despite the introduction of suicide prevention programs in Korea.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that the incidence rates of SA-related ED visits was increasing in female adolescents from 2016 to 2019. This finding is consistent with results reported in previous studies conducted in Korea about the increase in number of female teenagers engaging in suicidal behaviors, including SA as well as suicidal ideation and suicidal planning [ 6 , 29 ]. The increase in SAs among female seems to contribute to the stagnation of the suicide rate despite the introduction of suicide prevention programs in Korea.…”
Section: Discussionsupporting
confidence: 93%
“…Suicide is the leading cause of death among South Korean adolescents. A recent Korean study regarding adolescents who visited an emergency department after self‐harm found that the number of episodes increased greatly between 2015 and 2019 (Cheon et al, 2020). Although research interest in NSSI has grown rapidly, few studies have explored NSSI in Korean adolescents (Kim & Yu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results from the current study are partly consistent with the previous studies showing that the elevated severity of mental health symptoms in the early stages of the pandemic (March–April) decreased in mid-2020 and was recovered to the pre-pandemic level, which is an indication of psychological resilience [ 15 ]. According to previous studies using data of emergency department visits resulting from suicide attempts among Korean adolescents, suicide attempts in Korean adolescents increased between 2015 and 2019 [ 30 ], whereas in 2020, the overall trend of suicide attempts did not change significantly from before the pandemic [ 31 ]. Improved mental health outcomes among adolescents were also observed in other Asian countries during the pandemic and lockdown [ [32] , [33] , [34] , [35] ].…”
Section: Discussionmentioning
confidence: 99%